Die Wiener Stadtbücher 1395-1430, Teil 5: 1418-1421 - Neschwara, Christian (2018)
The Archive of the City of Vienna keeps three folio-volumes of a manuscript in conservation of her archive, which in common was marked as "Wiener Testamentsbücher" (Viennese Last Wills-Register). The source, comprising the period of 1395 to 1430, at this time was named "Stadtbuch", and this appoints the character of such registers, which served for registration of legal transactions in urban space. In total the "Stadtbuch" embodies more than 4.500 registrations, in most cases last wills ("Geschäfte"), but also a lot of registrations about transactions concerning private law as well as matters of pubic law.